Assessment of River Water Quality using Benthic Macroinvertebrates as Bioindicators of Hanumante River, Kathmandu Valley, Nepal - Uprety, Mahendra Prasad; Adhikari, Sarala; Awasthi, Mahesh Prasad; Raut, Gaurav Kumar; Sapkota, Ramesh Prasad (Journal of Institute of Science and Technology, 2024)
Benthic macroinvertebrates play a significant role in assessing the water quality of aquatic ecosystems. This study was conducted to assess the river water quality of the Hanumante River situated at Kathmandu Valley, Nepal using benthic macroinvertebrates as bioindicators. Altogether seventeen sites were monitored following a globally recognized multi-habitat sampling along the Hanumante River from Muhanpokhari to Narephant (Jadibuti) using a standard hand net with a frame width of 25 × 25 cm2, metallic frame with 500 µm mesh size. The collected macroinvertebrates were identified at the family level. A total of 10 orders, 33 families, and 4419 total individuals of macroinvertebrates were observed. Among all, the family Chironomidae (red) under order Diptera were the highest in number. The results showed that upstream sites were characterized by high taxa richness, abundance, and presence of pollution-sensitive taxa such as Ephemeroptera, Plecoptera, and Trichoptera, while Chironomidae, Tubificidae, and Simuliidae dominated downstream. The obtained results reflected that the water quality of the river in the upstream sites was comparatively better compared to the downstream. The water quality was deteriorating due to increasing human disturbances in the river, which demands the regular monitoring of water quality and aquatic biodiversity in the river.